Traditional and Non-traditional English Language Teaching Method Agreement In Accelerated Language Learning Based On Psycho-Pedagogical Principals - Jatautaitė, Dileta (Acta Paedagogica Vilnensia, 2004)
Research problem is how to formulate, ground and validate the basis and methods of intensive Lithuanian military teaching to the Standard English language course referring to already practiced and new nonstandard methods and verify their efficiency. The research object is: intensive and short-termed teaching of English to Lithuanian military. The research aim: to construct the content and the practical model of intensive Lithuanian military teaching to the English language and asses the acquisition of the Standard course. The aim of the article was to find out the effectiveness of non-traditional and traditional language teaching method agreement in teaching the military. The method agreement had to be used on the principles of psycho didactics. The methods which were used in the evaluation all four language skills (reading, speaking, writing and listening), by which the results were measured, proved the effectiveness of teaching military the intensive English language course. All those who participated in the research showed good results as it had been expected before starting the research. Language learning results were evaluated via four language skills. Learning was improved as the result of new challenging method combination based on psycho didactical principles. The investigation has also proved that the research teaching is not only memorization, but the understanding and creative solution in language learning based on communicative method usage in traditional and non-traditional method coordination. The method has claimed that it works equally well whether the object of the research is gifted or not. The optimal mental and psycho states have proved the importance in reaching good language learning results and thus accelerating the learning of the military. The result of all used and mentioned aspects has showed the effectiveness of the chosen method agreement.
Keywords: standard English; language teaching; learning; method; military